2008
DOI: 10.1002/smll.200700493
|View full text |Cite
|
Sign up to set email alerts
|

Mesoporous Silica Nanoparticles Improve Magnetic Labeling Efficiency in Human Stem Cells

Abstract: Tumblerlike magnetic/fluorescein isothiocyanate (FITC)-labeled mesoporous silica nanoparticles, Mag-Dye@MSNs, have been developed, which are composed of silica-coated core-shell superparamagnetic iron oxide (SPIO@SiO(2)) nanoparticles co-condensed with FITC-incorporated mesoporous silica. Mag-Dye@MSNs can label human mesenchymal stem cells (hMSCs) through endocytosis efficiently for magnetic resonance imaging (MRI) in vitro and in vivo, as manifested by using a clinical 1.5-T MRI system with requirements of si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
69
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(74 citation statements)
references
References 27 publications
4
69
0
Order By: Relevance
“…However, cell differentiation was investigated only qualitatively or restricted to certain lineages. Fluorescence-labelled biocompatible mesoporous silica nanoparticles were reported to have no effect on osteogenic and adipogenic MSC differentiation [21,31]. In contrast, some authors found a negative influence on osteogenic differentiation after treatment with biphasic calcium phosphate particles, related to particle release from bioceramics [32].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…However, cell differentiation was investigated only qualitatively or restricted to certain lineages. Fluorescence-labelled biocompatible mesoporous silica nanoparticles were reported to have no effect on osteogenic and adipogenic MSC differentiation [21,31]. In contrast, some authors found a negative influence on osteogenic differentiation after treatment with biphasic calcium phosphate particles, related to particle release from bioceramics [32].…”
Section: Discussionmentioning
confidence: 97%
“…Some authors reported an undisturbed differentiation capacity of MSC towards the osteogenic, adipogenic or chondrogenic lineage when treated with various particles [17,21,22]. In most of these studies, the investigation of the differentiation potential was limited, being only qualitative or restricted to only a small number of cellular differentiation markers.…”
Section: Introductionmentioning
confidence: 95%
“…Several types of magnetic-fluorescent nanocomposites have been developed [42][43][44][45][46][47]. Lu et al have prepared a silica encapsulated commercial ferrofluid with the thickness of the silica shell controlled to between 2 and 100 nm by changing the concentration of the TEOS precursor [16].…”
Section: Introductionmentioning
confidence: 99%
“…The antioxidant effect of MSN is related to their biocompatibility (22,30). In previous studies, it has been shown that MSN possesses biocompatibility features (21,31). These results show that MSN without affecting healthy tissues circulates in the bloodstream and when reaches to the tumor cells, exerts its inhibitory effects.…”
Section: Discussionmentioning
confidence: 85%